Deiksis Pragmatik pada Daftar Putar Booklist dalam Channel YouTube Maudy Ayunda - Alin Nida Millatina; Belia Putri Kunsiyanto; Melly Eka Putpri; Inung Lufiana; Najwa Khalisa Azahra; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Education is important because it provides knowledge and skills that are essential for self-development, character building, improving people's lives, and contributing to the progress of the nation and state. YouTube is a platform used by many people for entertainment and to relieve boredom. YouTube also offers a wide variety of videos and content, ranging from video blogs, entertainment videos, music, to educational videos. Pragmatics is a study that focuses more on what the speaker wants to convey through their speech, not just studying the meaning of words or phrases separately. In pragmatics, there are several terms of speech act analysis, implicature, deictics, presupposition, and politeness. In this study, the researcher analyzed the pragmatics of deictics. The research is titled “Pragmatic Deixis in the Booklist Playlist on Maudy Ayunda's YouTube Channel.” The researcher found three types of deixis, including 163 instances of personal deixis, 5 instances of place deixis, and 2 instances of time deixis. The research method used was qualitative description.